2015
DOI: 10.18517/ijaseit.5.6.594
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Imprinted Polymer (MIP) Based PVC-Membrane-Coated Graphite Electrode for the Determination of Heavy Metals

Abstract: A PVC membrane based on molecularly imprinted polymer (MIP) coated directly on graphite electrode for determination of heavy metals in real soil sample is describes. The composite membranes have been prepared by using methacrylic acid (MAA) as functional monomer and ethylene glycol dimethyl acrylate (EGDMA) as cross linker. MAA was chosen as a functional monomer, as it capable of strong electrostatic interactions with heavy metals. The chemical behaviour of the thin film (MIP) were characterized using Scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 10 publications
(9 reference statements)
0
5
0
1
Order By: Relevance
“…6. Research [11] reported the results from a Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS) tests. Based on the results of the EDS test showed that element C has the highest content.…”
Section: Resultsmentioning
confidence: 99%
“…6. Research [11] reported the results from a Scanning Electron Microscope (SEM) and Energy Dispersive Spectroscopy (EDS) tests. Based on the results of the EDS test showed that element C has the highest content.…”
Section: Resultsmentioning
confidence: 99%
“…Kelemahan metode analisis GC dan HPLC adalah perlakuan ekstraksi dan pemurnian di laboratorium yang membutuhkan pelarut dan waktu analisis yang lebih lama yang memungkinkan terdapatnya resiko kesalahan. Oleh karena itu, untuk mengatasi kekurangan tersebut saat ini sedang dikembangkan metode baru untuk analisis residu pestisida simazin dengan Molecular Imprinted Polymer (MIP) [5][6][7]. MIP adalah polimer sintetis dengan rongga yang spesifik untuk molekul target.…”
Section: Pendahuluanunclassified
“…Sensors are system elements that can capture and filter physical and chemical phenomena, then convert them into electrical signals in the form of electric current or voltage, generally known as electrodes. Currently, the use of electrochemical sensors in recognizing foreign objects in the surrounding environment has developed [7], [19], [20]. Related to previous research that has been done by other researchers, the novelty of this research is the method of making MIP and placing MIP on the surface of aluminum electrodes with the assumption that this material is a conductor that will facilitate ion transfer.…”
Section: Introductionmentioning
confidence: 99%